2014
DOI: 10.1007/s13277-014-2556-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of TP53 PIN3 polymorphism with breast cancer in Moroccan population

Abstract: TP53 is a tumor suppressor gene involved in cell cycle progression control, DNA damage repair, genomic stability, and apoptosis. Some polymorphisms in this gene have been associated with the development of a number of cancers including breast carcinoma. PIN3 Ins16bp polymorphism has been widely studied in different populations for an association with breast cancer risk. In most case-control studies, a duplicated allele has been more frequent in cases rather than controls but there are also inconsistent results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 51 publications
5
12
1
Order By: Relevance
“…Similar results have been found in the Iranian population by Faghani et al who reported a correlation between invasive ductal breast cancer and the PIN3 duplication polymorphism at 16 bp [41]. Contrary to our observations, studies carried out in the Moroccan, Croatian and Czech populations have not found any link between histological types and mutations in this gene [20,27,35]. These contradictory results may be explained by the ethnic and geographic origin.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Similar results have been found in the Iranian population by Faghani et al who reported a correlation between invasive ductal breast cancer and the PIN3 duplication polymorphism at 16 bp [41]. Contrary to our observations, studies carried out in the Moroccan, Croatian and Czech populations have not found any link between histological types and mutations in this gene [20,27,35]. These contradictory results may be explained by the ethnic and geographic origin.…”
Section: Discussionsupporting
confidence: 66%
“…PCR ampli cation conditions were previously described by Maarouf and al. [20]. The PCR products after electrophoresis on a 4.5% agarose gel showed a fragment of 119 bp for the A1 allele (wild type or no duplication) and a fragment of 135 bp for the A2 allele (Insert or 16-bp duplication).…”
Section: Genotyping Of Pin3 16-bp Duplicationmentioning
confidence: 92%
See 2 more Smart Citations
“…It responds to different cellular stress signals by regulating gene expression, which may lead to the induction of cell cycle arrest, apoptosis, senescence, DNA repair and/or metabolic modifications within the cell [18]. P53 inhibitor proteins include MDM2 and MDMX, and their increased turnover is a characteristic of many tumors [19].…”
Section: Retinoblastoma Initiation and Progressionmentioning
confidence: 99%